The Multifaceted Appearance of Supratentorial Ependymoma with ZFTA-MAML2 Fusion - Oon, Ming Liang; Hendriansyah, Lutfi; Pratiseyo, Patricia Diana; Wahjoepramono, Eka; Goh, Jian Yuan; Kuick, Chik Hong; Chang, Kenneth TE; Perry, Arie; Tan, Char Loo (Free Neuropathology, 2021)
Ependymomas are glial neoplasms with a wide morphological spectrum. The majority of supratentorial ependymomas are known to harbor ZFTA fusions, most commonly to RELA. We present an unusual case of a 9-year-old boy with a supratentorial ependymoma harboring a noncanonical ZFTA-MAML2 fusion. This case had unusual histomorphological features lacking typical findings of ependymoma and bearing resemblance to a primitive neoplasm with focal, previously undescribed myogenic differentiation. We discuss the diagnostic pitfalls in this case and briefly review the histological features of ependymoma with noncanonical gene fusions. Our report underscores the importance of molecular testing in such cases to arrive at the correct diagnosis. Supratentorial ependymomas with noncanonical fusions are rare, and more studies are necessary for better risk stratification and identification of potential treatment targets.